Impact of Microwave Treatment on Chemical Constituents in Fresh Rhizoma Gastrodiae (Tianma) by UPLC-MS Analysis - Qimeng Fan; Chaoyin Chen; Dingqi Xie; Shenglan Zhao (Journal of Chemistry)
Fresh Rhizoma Gastrodiae (Tianma) was processed in a microwave oven at 2450 MHz in order to study the effect on the main chemical component changes taking place during microwave treatment. It was found that microwave affected the chemical composition of Tianma. Seven compounds, including gastrodin, gastrodigenin (p-hydroxybenzylalcohol), p-hydroxybenzaldehyde, vanillyl alcohol, vanillin, adenine, and 5-hydroxymethylfurfural, were identified in this study. As major active compounds, the contents of gastrodin and gastrodigenin in MWT Tianma were both twice as much as those in raw Tianma. Besides, the MS data show that there are still some unidentified compositions in Tianma, and there are also many converted compounds in MWT Tianma, which is worthy of further work. The results have indicated that microwave treated fresh Tianma might be helpful in designing the processing of traditional Chinese medicine and the application of microwave technology in traditional Chinese medicine needs to be researched further in the future.